Effects of soybean oil and corn oil alone or in combination with Rumensin®, on methane and VFA production, in vitro - Riley, Jack G.; Newby, S.L. (Kansas State University. Agricultural Experiment Station, 2011)
Soybean oil or corn oil when fed at 0, 2, 4, or 6% of the ration did not significantly reduce methane production or alter the ratios of volatile fatty acids. Soybean oil was superior to corn oil in reducing methane, and soybean oil, produced a more desirable acetate:propionate ratio. Rumensin was compared at levels simulating 0, 15, and 30 grams per ton of complete ration. Rumensin at either concentration significantly reduced methane and significantly improved the acetate:propionate ratio.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Soybean oil; Corn oil; Rumensin; Methane; VFA production